Graphical Analysis of Overhead. - Jennings, Robert M. (The Accounting Review, 1966)
In cost accounting many of the biggest problems occur in the overhead element. One of the frequently posed overhead problems rise in consolidating substantial error in the absorption rate due to a volume change in operations. The usual text treatment leaves past operations uncorrected, simply alters the absorption rate to a new incorrect figure. This lets the error in the months of operation prior to the recognition of a need for some adjustment. A type of graphical analysis might be utilized as a simple but effective tool to clearly demonstrate the respective alternatives of either making an adjustment in the accounts and using a corrected rate or allowing the old figures to stand and simply routing your overhead application rate to a new basis designed to offset the past error by a counterbalancing error over the remaining financial period. However, graphical analysis vividly demonstrates the difference in the effect of the alternatives on absorbed cost during the planned production period.